2021
DOI: 10.1177/13694332211008316
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the TMD on the vibration of an offshore wind turbine considering three soil-pile-interaction models

Abstract: In this paper we propose the use of the power series method and the Newmark-Beta algorithm to study the mitigation by the tuned mass damper (TMD) of an offshore wind turbine(OWT). The monopile of the OWT is taken as slender beam buried in a homogeneous soil while the tower is considered as tapered slender beam. Mathematically, both monopile and tower are modeled as elastic Euler-Bernoulli beams, with a point mass at the tower top representing the rotor nacelle assembly (RNA). First of all, the power series met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…The mudline stiffnesses are determined such that the same mudline displacement ρ and rotation θ are obtained as with the P-y model. [21].…”
Section: Modelling Soil-pile Interactionsmentioning
confidence: 99%
“…The mudline stiffnesses are determined such that the same mudline displacement ρ and rotation θ are obtained as with the P-y model. [21].…”
Section: Modelling Soil-pile Interactionsmentioning
confidence: 99%
“…Te TMD can be divided into two categories according the structural form, including the support TMD installed in nacelle of steel wind turbine [17] and pendulum TMD suspended inside the tower [18]. As for the support TMD, Bin Zhao et al investigated the vibration control performance of a support TMD for steel WTT under wind-wave excitations, and the shaking table test results showed that TMD can efectively weaken the dynamic responses of steel WTT under the wind-wave loads [19].…”
Section: Introductionmentioning
confidence: 99%